The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1136/jnnp-2021-326184
|View full text |Cite
|
Sign up to set email alerts
|

The hypometabolic state: a good predictor of a better prognosis in amyotrophic lateral sclerosis

Abstract: BackgroundMalnutrition and weight loss are negative prognostic factors for survival in patients with amyotrophic lateral sclerosis (ALS). However, energy expenditure at rest (REE) is still not included in clinical practice, and no data are available concerning hypometabolic state in ALS.ObjectiveTo evaluate in a referral cohort of patients with ALS the prevalence of hypometabolic state as compared with normometabolic and hypermetabolic states, and to correlate it with clinical phenotype, rate of progression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
0
14
1
Order By: Relevance
“…Therefore, the epidemiological characteristics of ALS in Chinese are different from those in other countries. The mean age of onset in our study is 49.49 years old (SD 11.16), younger than patients form Japan and Europe, 61.0 16 and 63.79 years old 17 , respectively. However, in India, it is 51.6 years old 18 , lower than that in most other regions around the world.…”
Section: Discussioncontrasting
confidence: 44%
“…Therefore, the epidemiological characteristics of ALS in Chinese are different from those in other countries. The mean age of onset in our study is 49.49 years old (SD 11.16), younger than patients form Japan and Europe, 61.0 16 and 63.79 years old 17 , respectively. However, in India, it is 51.6 years old 18 , lower than that in most other regions around the world.…”
Section: Discussioncontrasting
confidence: 44%
“…The liver is a pivotal metabolic organ that acts as a hub that connects various organs, including skeletal muscle and adipose tissue [ 30 ]. Growing evidence suggests that dysregulated energy metabolism in patients with ALS and mouse models is closely correlated with metabolic abnormalities in disease progression and susceptibility [ 31 , 32 , 33 ]. It has been reported that the activity of Mdh is increased in the synaptosomes and homogenates from the spinal cord and motor cortex in hSOD1 G93A mice in the early stages of the disease [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypermetabolism identified via FDG-PET clearly occurs in skeletal muscle and low brain motor areas in ALS. [110][111][112][113][114][115] When added to the widespread evidence for increased resting energy expenditure in ALS detected via indirect calorimetry (including in early-stage patients), [116][117][118][119][120][121][122][123] hypermetabolism is one of the major documented ALS phenomena. While indirect calorimetry does not point to a specific mechanism, FDG-PET directly points to excessive transporter-mediated glucose uptake.…”
Section: Version 3 January 2023mentioning
confidence: 99%